Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Appendix A - Review - A.8 Solving Equations - A.8 Assess Your Understanding - Page A70: 17



Work Step by Step

On the left side of the equation, distribute $-$ (or subtraction) then combine like terms to obtain: $$ 8x - (2x + 1) = 3x - 10\\8x - 2x -1 = 3x - 10\\ 6x-1 = 3x - 10$$ Combine like terms by subtracting $3x$ to both sides first, then adding $1$ to both sides after: $$ 6x-1-3x = 3x - 10-3x\\ 3x-1=-10\\ 3x-1+1=-10+1\\ 3x=-9 $$ Dividing both sides by $3$ gives: $$x=-3$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.